2006
DOI: 10.1136/sti.2004.014381
|View full text |Cite
|
Sign up to set email alerts
|

Texting decreases the time to treatment for genital Chlamydia trachomatis infection

Abstract: Objective: To assess the effectiveness of a text message result service within an inner London sexual health clinic. Method: Demographic data, diagnoses, and time to diagnosis and treatment were collected over a 6 month period for patients receiving text messages and a matched standard recall group. Data on messages sent, staff time, and cost in relation to result provision were collected. Results: Over a 6 month period 952 text messages were sent. In the final month of analysis, 33.9% of all clinic results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 7 publications
(6 reference statements)
0
86
0
Order By: Relevance
“…The healthcare system is beginning to test and apply this technology in different ways in order to improve patient care. [17][18][19] In a qualitative study looking at asthma outpatient non-attendance, patients spontaneously brought up the subject of text messaging as a reminder of future appointments. 3 The present study is important because it attempted to investigate the feasibility of using a new innovation in health service delivery to reduce nonattendance.…”
Section: Introductionmentioning
confidence: 99%
“…The healthcare system is beginning to test and apply this technology in different ways in order to improve patient care. [17][18][19] In a qualitative study looking at asthma outpatient non-attendance, patients spontaneously brought up the subject of text messaging as a reminder of future appointments. 3 The present study is important because it attempted to investigate the feasibility of using a new innovation in health service delivery to reduce nonattendance.…”
Section: Introductionmentioning
confidence: 99%
“…General practitioners may be forced to institute treatment measures as intermediate solutions and often these prove sufficient to alleviate symptoms. Text messages are a well-described mode of communication in the medical literature and reported uses include reduction of anxiety of surgical patients' families in Taiwan [10], reduction of HbA1C in patients with type 2 diabetes in Korea [11] and decreasing time to treatment for genital Chlamydia in London [12]. Casey et al [2] reported that Irish patients interviewed would most like to be reminded of clinic appointment by phone (37%), followed by letter (36%), text message (34%) and only 6% by email.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the research has focused only on the 'effectiveness' of digital communication [18][19][20]. This may be because the direct costs to services of using text, mobile or internet communication appears low [21,22].…”
Section: Introductionmentioning
confidence: 99%